Tahap keberkesanan pengurusan penyenggaraan fasiliti bangunan di sektor awam Malaysia - Mat Deris, Mohd. Sabri (2007)
The purpose of this study is to measure the effectiveness of maintenance management of public facilities in Malaysia. As unfit workplaces for staff will give a negative impact to the government’s delivery system and nation development, effective maintenance of public sector facilities is therefore very important. The first objective of the study is to identify a framework of measurement for the effectiveness of maintenance management of public facilities in Malaysia. Second objective is to evaluate a status of the effectiveness of maintenance management of public facilities in Malaysia. From literature review, the author has identified the key parameters and elements to measure the effectiveness of maintenance management such as maintenance policy deployment & organization, maintenance approach, job planning & scheduling, information management and computerize maintenance management system (CMMS), spare part management, human resource management, contracting out management, financial aspect and continuous improvement. In this study, data were collected through random interviews and questionnaire surveys from various categories of public departments in Wilayah Persekutuan Kuala Lumpur such as offices, schools, army camps and etc. Data analysis was carried out by applying both statistical descriptive and inferential techniques such as Summarize frequencies, Crosstabulation and Pearson Correlation methods. The output from the data analysis was computed through SPSS software program and Microsoft Excel 2003. The findings show that compliance aspects of main elements for government buildings in Wilayah Persekutuan Kuala Lumpur is still lacking where majority (98%) of the samples do not achieve an excellence level of the effective maintenance indicators.